Analysis Of TCP Congestion On Random And Structured RSU Distribution For VANET - et. al., Ajay Kumar, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the significant issues is that can limit the capacity of VANET would be network congestion. The first phase is congestion management, congestion analysis is the focus of the article. We suggest cumulative parameters that can take into account the total structure of the system, including TCP traffic energy used by each node, throughput, the delay, cumulative distribution time and congestion window. The cumulative parameter can reliably, quickly, and instantaneously detect channel congestion by the Control room and eliminating the flaws of using the different variables to reduce the channel congestion. Besides that, the article suggests a necessary, but robust infrastructure-based approach by using the TCPVegas technique that can normalize these variables through the same aspect, resulting in the normalization of the cumulative value. This article helps to manage the communication traffic in VANET so that the High Priority Message reaches the destination with minimal time. This approach also helps to reduce accidents by getting information on time.